Usefulness of Surgical Media Center as a Cataract Surgery Educational Tool - Tomoichiro Ogawa; Takuya Shiba; Hiroshi Tsuneoka (Journal of Ophthalmology)
Purpose. This study retrospectively analyzed cataract surgeries to examine the usefulness of Surgical Media Center (SMC) (Abbott Medical Optics Inc.), a new cataract surgery recording device, for training of cataract surgery. Methods. We studied five hundred cataract surgeries conducted with a phacoemulsification system connected to the SMC. After surgery, the surgical procedures were reviewed, with changes in aspiration rate, vacuum level, and phaco power displayed as graphs superimposed on the surgical video. We examined whether use of SMC is able to demonstrate the differences in technique between experienced and trainee operators, to identify inappropriate phacoemulsification techniques from analyzing the graphs, and to elucidate the cause of intraoperative complications. Results. Significant differences in the time taken to reach maximum vacuum and the speed of increase in vacuum during irrigation and aspiration were observed between experienced and trainee operators. Analysis of the graphs displayed by SMC detected inappropriate phacoemulsification techniques mostly in cases operated by trainee operators. Conclusions. Using SMC, it was possible to capture details of cataract surgery objectively. This recording device allows surgeons to review cataract surgery techniques and identify the cause of intraoperative complication and is a useful education tool for cataract surgery.